Comparison of conventional and Alltech Beef PN finishing programs: meat color characteristics - Kelsey Phelps; K. A. Miller; Cadra L. Van Bibber-Krueger; J. Jennings; James S. Drouillard; John M. Gonzalez; Brandon E. Depenbusch (Kansas Agricultural Experiment Station Research Reports, 2014)
To maximize efficiency and profit when producing beef, American producers currently employ a multitude of production programs that use feed additives such as Rumensin or Tylan (Elanco Animal Health, Greenfield, IN) and growth promotants such as implants and Optaflexx (Elanco Animal Health). Rumensin and Tylan fed in combination can improve average daily gain and feed efficiency, and utilizing growth promotants enhances feed efficiency, average daily gain, hot carcass weight, and yield grades of carcasses. Although these products improve production efficiency, they can affect meat quality characteristics such as retail shelf life, necessitating better understanding of how management decisions in the feedlot can affect retail display. The Alltech PN Beef Program (Alltech Inc., Nicholasville, KY) consists of two products that are designed to replace components of a conventional feedlot diet. The PN Beef Receiver is intended to be fed during the step-up period of feeding, whereas PN Beef Finisher is intended to be fed during the remainder of finishing period. Because both products are new feed alternatives, the objective of this study was to compare the effects of the Alltech PN Feed Program to a conventional diet on fresh meat retail shelf life color when both diets were fed with or without implants and Optaflexx.
Keywords: Cattlemen& #x27; s Day; 2014; Kansas Agricultural Experiment Station contribution; no. 14-262-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1101; Beef Cattle Research; 2014 is known as Cattlemen& #x27; s Day; Beef; Feed additives; Growth promotants; Meat quality; Color; Shelf life; Altech PN Beef Program